The Role of Saudi Nurses in the Care of Patients with Obsessive-Compulsive Disorder: A Systematic Review - Basri, Zakyah; Benkafo, Abeer; Aloufi, Nouf; Aladah, Rawan; Aljezani, Eman; Aljezani, Fardous; Alamri, Sameeha; Aljezani, Fatma (Journal of Ecohumanism, 2024)
This systematic review investigates the pivotal, yet underexplored, role of Saudi nurses in caring for patients with Obsessive-Compulsive Disorder (OCD), a prevalent mental health condition that profoundly impacts individuals’ daily lives and well-being. Given the rising mental health challenges in Saudi Arabia and the cultural stigma often surrounding mental health care, it is essential to better understand and strengthen the support provided by nurses—frequently the frontline caregivers in OCD treatment. The study synthesizes existing research on the contributions of Saudi nurses to OCD care across multiple domains, including patient assessment, therapeutic interventions, and family support, which is particularly significant within the Saudi cultural context. By examining current practices and the challenges nurses face, such as limited mental health training, lack of institutional resources, and cultural barriers to open discussions of mental health, this review reveals structural limitations that impact the effectiveness of nursing care. At the same time, the analysis highlights the resilience and adaptability of Saudi nurses, who frequently operate with limited specialized resources and navigate considerable obstacles in their work. The findings underscore an urgent need for a culturally informed approach to OCD care that combines enhanced mental health training specific to OCD with strengthened institutional support to address the unique challenges faced by Saudi nurses. This review calls on healthcare policymakers to prioritize mental health within the Saudi healthcare system and advocates for developing comprehensive mental health nursing frameworks that integrate cultural sensitivity with clinical expertise. By providing a nuanced understanding of Saudi nurses’ roles in OCD care, this study illuminates the specific barriers they face and suggests pathways to improve mental health care quality across Saudi Arabia. Ultimately, it establishes a foundation for future research aimed at transforming mental health nursing practices to better meet the complex needs of OCD patients in ways that are both culturally respectful and clinically effective.